Probiotic properties of Bacillus licheniformis HN318 and comparison of the effects of its bacterial cells and cultures on growth, immunity and disease resistance of hybrid grouper (Epinephelus polyphekadion♂ × Epinephelus fuscoguttatus♀) - Cao, Zhenjie; Yang, Qiaoli; Kang, Aie; Wang, Guotao; Li, Pengshuo; Qiu, Guiping; Wang, Jinge; Liu, Chunsheng; Sun, Yun (Frontiers in Marine Science, 2025)
IntroductionBacillus species are probiotics commonly utilized in aquaculture to enhance aquatic animal growth, inhibit pathogens, and strengthen immunity. However, research comparing the effects of probiotic bacterial cells and cultures is limited. This study aimed to evaluate the probiotic potential of Bacillus licheniformis strain HN318 and compare its impact on growth, immunity, and disease resistance in hybrid grouper when administered as bacterial cells or cultures.MethodsThe study involved assessing the auto-aggregation capability, gastrointestinal stress resistance, and safety of HN318. Enzymatic activities and antibacterial properties of HN318 cultures and bacterial cells were also compared. Hybrid grouper were fed with HN318 cultures and bacterial cells for 8 weeks, and their growth, feed utilization, immune responses, and survival rates upon challenge with Vibrio harveyi were evaluated. Additionally, the expression of immune-related genes was analyzed.ResultsHN318 exhibited high auto-aggregation and gastrointestinal stress resistance, and was found to be safe for use in aquaculture. Cultures of HN318 displayed higher protease, amylase, and antibacterial activities compared to bacterial cells. Both forms significantly improved growth and feed utilization in hybrid grouper. Notably, HN318 cultures induced higher levels of immune enzymes and activities, and provided better protection against V. harveyi challenge, with a higher relative percent survival compared to bacterial cells. Furthermore, HN318 cultures upregulated the expression of immune-related genes more than bacterial cells.DiscussionThis study highlights the potential of both HN318 cultures and bacterial cells as immune enhancers for hybrid grouper. However, HN318 cultures demonstrated superior probiotic properties, including higher enzymatic activities, antibacterial properties, and immunomodulatory effects. These findings provide new insights and references for the diverse application forms of probiotics in aquaculture, suggesting that cultures may be more effective than bacterial cells in enhancing the health and performance of aquatic animals.